2009
DOI: 10.1016/j.yjmcc.2009.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Dietary ω-3 fatty acids alter cardiac mitochondrial phospholipid composition and delay Ca2+-induced permeability transition

Abstract: Consumption of ω-3 fatty acids from fish oil, specifically eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), decreases risk for heart failure and attenuates pathologic cardiac remodeling in response to pressure overload. Dietary supplementation with EPA+DHA may also impact cardiac mitochondrial function and energetics through alteration of membrane phospholipids. We assessed the role of EPA+DHA supplementation on left ventricular (LV) function, cardiac mitochondrial membrane phospholipid composition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
90
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(97 citation statements)
references
References 50 publications
4
90
2
1
Order By: Relevance
“…The impact on intracellular calcium handling is particularly noteworthy. Stanley et al ( 177,179,180 ) recently identifi ed the mitochondrial permeability transition pore (MPTP) as a target for 3 PUFA regulation. MPTP is a large-diameter, high-conductance, voltagedependent channel that allows passage of water, ions, and molecules up to 1.5 kDa.…”
Section: Pufa Regulation Of Cardiomyocyte Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact on intracellular calcium handling is particularly noteworthy. Stanley et al ( 177,179,180 ) recently identifi ed the mitochondrial permeability transition pore (MPTP) as a target for 3 PUFA regulation. MPTP is a large-diameter, high-conductance, voltagedependent channel that allows passage of water, ions, and molecules up to 1.5 kDa.…”
Section: Pufa Regulation Of Cardiomyocyte Functionmentioning
confidence: 99%
“…Findings that dietary SDA lowers some infl ammatory markers suggest this dietary source of 3 PUFA will be useful in modulating infl ammatory factors linked to CVD. DHA, however, has a greater capacity to regulate cardiac mitochondrial MPTP than other 3 PUFA ( 177,179,180 ). This is important for ventricular fi brillation and SCD ( 177,180,(230)(231)(232).…”
Section: Pufa From Plants Algae or Yeastmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, IFN-a and ribavirin treatment can further lead to EPA depletion . Supplementation with DHA alone or both DHA and EPA significantly delays Ca 2+ -induced MPTP opening in normal and hypertrophied myocardium (O'Shea et al, 2009;Khairallah et al, 2010). These changes were accompanied by an increase in DHA and EPA level in mitochondrial phospholipids and decreased AA level (Khairallah et al, 2010).…”
Section: Vitamin C E and Eicosapentaeoic Acid Supplementationmentioning
confidence: 95%
“…Cardiolipin is composed of four linoleic acid side chains, which is essential for normal mitochondrial respiration; however, substitute such as long chain saturated and monounsaturated fatty acids weaken mitochondrial function (O'Shea et al, 2009). Recent study has shown that increased saturated fatty acids and cholesterol associated with alteration in mitochondrial membrane and cardiolipin oxidation, which are required for HCV replication (Roe et al, 2011).…”
Section: Vitamin C E and Eicosapentaeoic Acid Supplementationmentioning
confidence: 99%